MODERNISASI BERAGAMA: PERAN GURU, KEPALA MADRASAH DAN PENGAWAS - Fajar Senjaya (Madaris: Jurnal Guru Inovatif, 2021)
Religious modernization is life many peoples with behavior to teachings religion influenced by chance politic system, religion, economy psychology, science, advances on technology and information. Which one, there is impact float to the surface by this revolution 4.0 is make it disposed generation have characteristic skeptic and scornful. Have depended on the technology and then to respect at hight privation. Therefore, we have to become aware of to be right, the generation have to educated with creative method, be different with education method for before generation. A technology development is technology information be like that very quickly to rub against or be chance function and a teacher role from teacher be on duty to extend learning be facilitator to give study easly. For that matter a good relation between a teacher like educator, school leader, and school supervisor to be education the next generation.